Early grade prediction using profile data - Iqbal, Sumaiya; Muntaha, Mahjabin; Natasha, Jerin Ishrat; Sakib, Dewan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.